Marketing Communication Strategy in ImprovingBrand Awareness Via Instagram - Pertiwi, Ratu; Sigit, Ridzki Rinanto (Peneliti.net, 2024)
This research aims to understand the implementation of the communication mix via Instagram (customer-based brand equity analysis at Uniwis Lombok). This research uses a qualitative approach. In this research, researchers used in-depth interview and observation techniques. The data analysis method used is data reduction. The results of the research show that the application of the marketing communication mix via Instagram through customer-based brand equity analysis consists of 4 (four) stages, namely Uniwis' brand loyalty is unique because the owner of Uniwis comes from the West Sumatra region, not from Lombok, while the products sold are products typical of Lombok, then Uniwis is the pioneer of woven ties, the next stage is brand performance, namely Uniwis really pays attention to the design of the products produced so that they still look fashionable with an ethnic touch, then the selection of strong and good quality materials, cotton thread with natural dyes and brand imagery, fabric Weaving is a cultural heritage, Uniwis participates in preserving cultural heritage by mixing and matching modern products and woven fabrics. The next stage is brand customer judgments, namely Uniwis really pays attention to the neatness of the products produced and brand customer feelings, namely customers will feel exclusive by using woven ties from Uniwis because only 1 tie is produced from 1 woven material, meaning only 1 tie with that pattern. then the final stage of brand resonance, repeat purchases by customers both for their own use and as souvenirs for relatives both domestically and abro